DNA hypomethylation induces a DNA replication-associated cell cycle arrest to block hepatic outgrowth in uhrf1 mutant zebrafish embryos - Jacob, Vinitha; Chernyavskaya, Yelena; Chen, Xintong; Tan, Poh Seng; Kent, Brandon; Hoshida, Yujin; Sadler, Kirsten C. (Development (Cambridge), 2015)
UHRF1 (ubiquitin-like, containing PHD and RING finger domains, 1) recruits DNMT1 to hemimethylated DNA during replication and is essential for maintaining DNA methylation. uhrf1 mutant zebrafish have global DNA hypomethylation and display embryonic defects, including a small liver, and they die as larvae. We make the surprising finding that, despite their reduced organ size, uhrf1 mutants express high levels of genes controlling S-phase and have many more cells undergoing DNA replication, as measured by BrdU incorporation. In contrast to wild-type hepatocytes, which are continually dividing during hepatic outgrowth and thus dilute the BrdU label, uhrf1 mutant hepatocytes retain BrdU throughout outgrowth, reflecting cell cycle arrest. Pulse-chase-pulse experiments with BrdU and EdU, and DNA content analysis indicate that uhrf1 mutant cells undergo DNA re-replication and that apoptosis is the fate of many of the re-replicating and arrested hepatocytes. Importantly, the DNA re-replication phenotype and hepatic outgrowth failure are preceded by global loss of DNA methylation. Moreover, uhrf1 mutants are phenocopied by mutation of dnmt1, and Dnmt1 knockdown in uhrf1 mutants enhances their small liver phenotype. Together, these data indicate that unscheduled DNA replication and failed cell cycle progression leading to apoptosis are the mechanisms by which DNA hypomethylation prevents organ expansion in uhrf1 mutants. We propose that cell cycle arrest leading to apoptosis is a strategy that restricts propagation of epigenetically damaged cells during embryogenesis.